Valence states of single Au atoms dictate the catalytic activity of Au1/CeO2(100). Issue 82 (28th September 2022) - Liu, Rui; Qu, Weiye; Hu, Xiaolei; Chen, Junxiao; Dong, Yangyang; Xu, Dongrun; Liu, Jing; Ma, Zhen; Tang, Xingfu
Abstract : The valence state of single Au atoms anchored on CeO2 (100) is tuned and the catalytic activity of Au1 /CeO2 (100) in CO oxidation increases by one order of magnitude as the valence state of Au decreases from +0.93 to +0.27. Abstract : We tune the valence state of single Au atoms anchored on CeO2 (100) by treating the catalyst in H2 at different temperatures and obtain a series of Au1 /CeO2 (100). The transition from Au1 +0.9 to Au1 +0.3 leads to an enhancement of the CO oxidation activity of Au1 /CeO2 (100) by one order of magnitude. This work is of significance for an in-depth understanding of reaction mechanisms and rational design of high-performance catalysts.